Existence of solutions to a discrete problems for fourth order nonlinear p-Laplacian via variational method - Omar Hammouti; Abdelrachid El Amrouss (Boletim da Sociedade Paranaense de Matemática, 2022)
We consider the boundary value problem for a fourth order nonlinear p-Laplacian difference equation and to prove the existence of at least two nontrivial solutions. Our approach is mainly based on the variational method and critical point theory. One example is included to illustrate the result.